Can Christensen’s assumption that the ‘Innovator’s Dilemma’ is the key reason companies lose market position, be applicable to all industries or is it technology centric? - Jennings, Harvey (2017)
The purpose of this dissertation is to identify if the theory proposed by Christensen in his work the Innovator’s Dilemma can be applied to industries outside of the direct technological sphere on which he focuses. The energy and food and drink sectors have been chosen for this study. The dissertation will assess the relevance of innovation studies in the wider business environment and to understand how this aspect of business management influences a firm’s business strategy. Christensen also places a lot of emphasis on the role of the consumer in the innovation process and this will also be an interesting area of study. To answer this question, a literature review will first be completed to identify relevant gaps that can be explored through research questions. Primary research will also be carried out in the form of semi-structured interviews to gain insight in to the perception of the consumer and innovation within firms. These interviews will be used in case studies to assess the applicability of Christensen’s theory and to incorporate secondary research to support our arguments. The results of the work indicated that the energy sector was in a state that meant the innovator’s dilemma could become a fundamental theory to form an innovation strategy around in the near future with the renewable energy revolution. The drinks sector however fell short, despite the necessary involvement of innovation and responsiveness to consumer demand. The conclusion was that Christensen’s theory could be applied to some extent in the wider business environment but required the sector to be susceptible to fundamental change in some form. The drinks industry for instance showed no real potential for disruptive innovations, as it is difficult to change these products drastically and therefore meant that the principles of the theory could not be applied.